DOES ELEMENTARY SCHOOL TEACHER’S PERFORMANCE MATTER? - Muhamad Afandi; Sri Wahyuningsih; Linda Ika Mayasari (Jurnal Cakrawala Pendidikan, 2021)
The performance of teachers in realizing holistic education can be observed from how the teachers prepare, implement, and evaluate the learning process or their pedagogic knowledge. This study aims to examine the teachers’ ability to plan, implement and evaluate to assess their performance in the elementary school learning process based on tenure and gender. This research is a quantitative study with direct observation, which was conducted on 162 elementary school teachers from 30 public elementary schools in Semarang, Indonesia. Data were collected using assessment sheets. The observer was the principal which belonged to the same school as the respondent. The data were then validated using Pearson's correlation based on group tenure and gender. The instrument was analyzed using structural equation modelling (SEM) and showed that the imposition of the confirmatory factor analysis (CFA) was achieved more than a critical value of .50 which meant that the construct was valid and reliable. The understanding on teachers’ performance was indicated by teachers’ activities in preparing their class. This study found that there was no significant correlation between teachers’ performance and teaching experience or that and gender.